Advanced Drug Delivery. Edited by Ashim K. Mitra, Chi H. Lee, Kun Chen. Issue 1 (18th September 2014) - Barbu, Eugen
<x xml:space="preserve">Abstract</x> Wiley, Hoboken 2014. 530 pp., hardcover, $125.00.—ISBN 978‐1‐118‐02266‐5<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>